Tourism in the Mountains of Central Kerala (South India): at the Crossroads of Attitudes Towards Forest Populations - Lucie Dejouhanet (Revue de Géographie Alpine)
In South India the term “Adivasi” (original inhabitants) designates forest dwellers, defined in the Constitution of India as Scheduled Tribes, who live in the Ghat mountains and their foothills. These populations have been ascribed two essentialist visions: preserved tribes living in harmony with nature and backward peoples who need to be educated so that they can be integrated into Indian society. These two visions coexist in how the mountain-dwelling Adivasi are perceived today by tourists as well as by the inhabitants of the plains and cities. This article underscores just how burdensome this past legacy is when observing these mountain areas and in the attitudes towards their inhabitants. Through several examples of tourist sites in Kerala, this article analyses the place accorded to the mountain Adivasi in the collective and tourist imagination, the role assigned to the local populations in tourist development, and how tourism brings out the hierarchical and inegalitarian social relations existing within forest society.